2018
DOI: 10.4317/medoral.22329
|View full text |Cite
|
Sign up to set email alerts
|

miR-1226 detection in GCF as potential biomarker of chronic periodontitis: A pilot study

Abstract: BackgroundThe study and identification of new biomarkers for periodontal disease, such as microRNAs (miRNAs), may give us more information about the location and severity of the disease and will serve as a basis for treatment planning and disease-monitoring. miRNAs are a group of small RNAs which are involved in gene regulation by binding to their messenger RNA target (mRNA). In this pilot study, the procedure for purifying miRNAs from gingival crevicular fluid (GCF) was, for the first time, described. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 29 publications
(37 reference statements)
2
39
2
1
Order By: Relevance
“…By comparing the genome-wide microRNA expression in healthy and periodontitis-affected tissues, a large set of differential microRNA expression has been identified 8 , indicating the involvement of microRNAs in this disease. The specific functionality of microRNAs in periodontitis pathogenesis remains largely unexplored, except for a recent study demonstrating that miR-1226 in gingival crevicular fluid can serve as a potential biomarker for periodontitis 14 . However, the molecular mechanism of the action that relates miR-1226 to periodontitis is still unspecified.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the genome-wide microRNA expression in healthy and periodontitis-affected tissues, a large set of differential microRNA expression has been identified 8 , indicating the involvement of microRNAs in this disease. The specific functionality of microRNAs in periodontitis pathogenesis remains largely unexplored, except for a recent study demonstrating that miR-1226 in gingival crevicular fluid can serve as a potential biomarker for periodontitis 14 . However, the molecular mechanism of the action that relates miR-1226 to periodontitis is still unspecified.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Saito et al investigated 600 miRNAs in GCF and found that they had a different profile compared to GCF in healthy subjects (Saito et al, 2017). The expression of miR-1226 in GCF in patients with severe chronic periodontitis was significantly down-regulated (Mico-Martinez et al, 2018) while other groups reported that miRNAs associated with inflammation (e.g., miR-146a and miR-155) were significantly up-regulated in chronic periodontitis with type 2 diabetes. Furthermore, pilot studies have reported increased expression of miR-143-3p (Nisha et al, 2019), miR-381-3p (Fujimori et al, 2019) in chronic periodontitis patients.…”
Section: Diagnostic Devices Salivary Proteome and Salivary Genomementioning
confidence: 99%
“…Due to the scarcity of studies on miRNAs in GCF and saliva (Saito et al, 2017;Atsawasuwan et al, 2018;Mico-Martinez et al, 2018;Radovic et al, 2018;Fujimori et al, 2019;Al-Rawi et al, 2020) further studies are still needed. Wearable sensors in the oral cavity may allow detection of miRNA changes, which may be useful for more detailed diagnosis and tracking of dynamics in periodontitis.…”
Section: Diagnostic Devices Salivary Proteome and Salivary Genomementioning
confidence: 99%
“…According to Mico et al [81], epigenetic regulation by miRNAs has not yet been studied in periodontal disease using crevicular fluid. They analyzed the possible use as biomarkers of six miRNAs: miR-671, miR-122, miR-1306, miR-27a, miR-223, and miR-1226.…”
Section: Mirnasmentioning
confidence: 99%